2015
DOI: 10.1002/adma.201502754
|View full text |Cite
|
Sign up to set email alerts
|

Polarization‐Mediated Thermal Stability of Metal/Oxide Heterointerface

Abstract: A polarization-mediated heterointerface is designed to research the thermal stability of magnetic metal/oxide interfaces. Using polarization engineering, the thermal stability of the interface between BiFeO3 and CoFeB can be improved by about 100°C. This finding provides new insight into the chemistry of the metal/oxide heterointerface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
5
11
0
Order By: Relevance
“…However, poor stability of the BFO/CoFeB interfaces seriously hindered the increase of giant magnetoresistance signal. Later, Zhang et al explored the thermal stability of the BFO/CoFeB interface [ 129 ] and revealed the physical mechanism. It demonstrated that the difference of oxygen vacancies induced by BFO polarization direction was the key that influenced the thermal stability.…”
Section: Application Of Bfomentioning
confidence: 99%
“…However, poor stability of the BFO/CoFeB interfaces seriously hindered the increase of giant magnetoresistance signal. Later, Zhang et al explored the thermal stability of the BFO/CoFeB interface [ 129 ] and revealed the physical mechanism. It demonstrated that the difference of oxygen vacancies induced by BFO polarization direction was the key that influenced the thermal stability.…”
Section: Application Of Bfomentioning
confidence: 99%
“…However, the DMI coupling can only occur in some special situations . On the other hand, in the BFO films with different polarization fields, the migration of oxygen vacancies may affect the oxidation level of the thin films neighboring to BFO . If we deposit a FM/HM structure on a BFO film, the different polarization fields of BFO should affect SOT through the indirect control of the oxidation level in the FM layer, which is completely different from previous studies on PMN‐PT, ionic liquid gate, and BTO …”
Section: Introductionmentioning
confidence: 61%
“…As shown in Figure S1a,b, Supporting information, the polarization field in BFO hetero is in P up state, while the one in S‐BFO hetero is in P down state. Considering oxygen vacancies are usually formed at the side with negative polarization bound charges, the top surface of BFO can be modulated into oxygen‐rich or oxygen‐poor states with different directions of spontaneous polarization fields . The amount of oxygen vacancies at the surface of BFO in S‐BFO hetero should be larger than that in BFO hetero .…”
Section: Resultsmentioning
confidence: 99%
“…The optimal oxidation of Co increases the 3d z 2 electrons, enhancing the PMA. The polarization can modulate the amounts of oxygen ions and their charge state at the PZT/Co heterointerface, [ 14,19,34–36 ] which plays a key role in the modulation of the PMA. [ 14,28,33 ]…”
Section: Resultsmentioning
confidence: 99%